Exploring the food taboo among fisherman families in Bulukumba District, South Sulawesi Province, Indonesia - Akbar, Hairil; Oruh, Shermina; Kamaruddin, Syamsu A.; Agustang, Andi (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Food taboo is one of the social phenomena that can influence people’s health status, including women in fisherman families. Some types of food categorized as taboo may contain high nutrients. Food taboo practices still occur because people are afraid that bad things will happen if they ignore them. Objective: This study aimed to explore the food taboo among pregnant, breastfeeding, and adult women in Bira Village, Bulukumba District, South Sulawesi Province, Indonesia. Methods: This study employed a phenomenological design. Eight participants were selected using the purposive sampling method. Data were collected in 2022 using semi-structured interviews and were analyzed using summative content analysis using NVivo software. Results: Several types of food were categorized as taboo, such as Lela fish, moringa fruit, pineapple, stingray, moringa leaf, squid, and mango. Most participants agreed that they just follow what the older people suggest, which might not make sense since all those foods contain many nutritional ingredients. Conclusion: The study findings serve as an input for public health professionals and other related stakeholders to address this cultural issue and provide understanding to the community not to avoid taboo food, which is essentially beneficial for their health.